Democracy in a Pandemic Participation in Response to Crisis - Hughes, Tim; Adams, Lizzie; Obijiaku, Charlotte; Smith, Graham (University of Westminster Press, 2021)
Covid-19 has highlighted limitations in our democratic politics - but also lessons for how to deepen our democracy and more effectively respond to future crises. In the face of an emergency, the working assumption all too often is that only a centralised, top-down response is possible. This book exposes the weakness of this assumption, making the case for deeper participation and deliberation in times of crises. During the pandemic, mutual aid and self-help groups have realised unmet needs. And forward-thinking organisations have shown that listening to and working with diverse social groups leads to more inclusive outcomes. Participation and deliberation are not just possible in an emergency. They are valuable, perhaps even indispensable. This book draws together a diverse range of voices of activists, practitioners, policy makers, researchers and writers. Together they make visible the critical role played by participation and deliberation during the pandemic and make the case for enhanced engagement during and beyond emergency contexts. Another, more democratic world can be realised in the face of a crisis. The contributors to this book offer us meaningful insights into what this could look like.